Synergism of antioxidant action of vitamins E, C and quercetin is related to formation of molecular associations in biomembranes1. Issue 36 (4th May 2015) - Fabre, Gabin; Bayach, Imene; Berka, Karel; Paloncýová, Markéta; Starok, Marcelina; Rossi, Claire; Duroux, Jean-Luc; Otyepka, Michal; Trouillas, Patrick
<x xml:space="preserve">Abstract</x> Vitamins and polyphenols form non-covalent complexes in biomembranes enhancing the global antioxidant status through synergism.